Understanding mediation as an out-of-judicial procedure for the settlement of civil-legal and labor disputes - Mahnovskyi I. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose.The purpose of the work is to analyze the understanding of mediation as a special out-of-court procedure for the settlement of civil and labor disputes. Methodology. The methodology includes a comprehensive analysis and generalization of the available scientific and theoretical material and the formulation of relevant conclusions and recommendations. The following methods of scientific reseach have been implemented: terminological, logical-semantic, functional, system-structural, logical-normative. Results.In the research process, it was recognized that among the practice of dissemination, which is demanded by time, effective tools based on safe reconciliation and mutually beneficial agreement, which are distinguished by their flexibility, extrajudicial, independent, alternative ways of settling civil and labor disputes and conflicts, in the domestic legal mechanism of ensuring human rights, mediation is becoming more and more widespread. The formation, adaptation and development of mediation in Ukraine are accompanied by national character and features, which will contribute, taking into account the standards in this field of foreign experience, to the development of appropriate professional approaches and competencies for the effectiveness of the legal regulation of the procedure for its application. Originality.In the process of research, based on the generalization of positive experience, the importance and effectiveness of mediation as a special out-of-court settlement procedure based on peaceful resolution and ag-reement of civil and labor disputes has been proven. Practical significance. The results of the research can be used in law-making and law-enforcement activities during the development of proposals for improving the legal mechanism of the out-of-court procedure for the settlement of civil and labor disputes.